'That teacher really likes me' - Student-teacher interactions that initiate teacher expectation effects by developing caring relationships. (August 2022) - Johnston, Olivia; Wildy, Helen; Shand, Jennifer
Abstract: Teacher expectations are associated with student academic achievement, but no research has generated new theory that explains how teacher expectation effects occur from students' perspectives. A substantive theory explaining the process through which students reconcile with their teachers' expectations is presented in this paper, emphasising the role of caring student-teacher relationships in teacher expectation effects on academic achievement. The theory was constructed with 25 grade 10 participants across three Western Australian secondary schools, with data including 100 interviews and 175 classroom observations. The analysis and synthesis of the data confirmed that the students acted in ways that they reflected improved their academic attainment when their teachers communicated high expectations of them. Noddings' enduring philosophy of the 'ethic of care' is used as a discussion framework, emphasising implications for how teachers practise and learn to interact with their students so that they can initiate positive teacher expectation effects on student learning. Highlights: Students experienced their teacher expectation effects on their academic success. High teacher expectations were appraised when teachers conveyed care. a new theory explains how teacher expectation effects occur through teacher care. The Ethic of Care and reciprocal relationships frames discussion of findings. Informs teacher learning and practice for interacting to convey high expectations.